Hubungan antara strategi pembelajaran dan kemampuan pronunciation - Toni Indrayadi (Universitas Putera Batam, 2026)
This study aims to investigate the pronunciation learning strategies (PLS) and pronunciation performance of Indonesian EFL students and to examine their correlation. A correlation design, adapting questionnaires of Tseng et al (2006) vocabulary learning strategies, which were developed from Eckstein (2007) and test was employed in this study. 68 students from the English department at one higher education institution in Jambi, Indonesia, were recruited using convenience sampling. Descriptive statistical analysis was run to analyze the level of students PLS and pronunciation performances. While inferential statistics of Pearson product-moment to examine the relationship between the two variables. The results revealed that the undergraduate students were at a medium level in using PLS, but cognitive is the highest among the strategies. The participants also performed well in terms of accuracy and intelligibility. The Significant correlation was found between PLS and both accuracy and intelligibility, and pronunciation performances. This study has a positive impact on pronunciation learning as it can be a foundation for lectures and students.